2013
DOI: 10.1093/ejcts/ezt440
|View full text |Cite
|
Sign up to set email alerts
|

Can maximal inspiratory and expiratory pressures during exercise predict complications in patients submitted to major lung resections? A prospective cohort study

Abstract: The measurement of PImax at the mouth during exercise represents an additional parameter that can be used to refine risk stratification of lung resection candidates and to identify patients who may benefit from inspiratory muscle training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…IMT positively enhances respiratory muscle strength, which reflects the relative load for breathing, coughing, and huffing (14,15). Moreover, Sutton et al showed that improved forced expiration maneuvers could be more effective than coughing for improving clearance of bronchoalveolar hyper-secretions (16).…”
Section: Discussionmentioning
confidence: 99%
“…IMT positively enhances respiratory muscle strength, which reflects the relative load for breathing, coughing, and huffing (14,15). Moreover, Sutton et al showed that improved forced expiration maneuvers could be more effective than coughing for improving clearance of bronchoalveolar hyper-secretions (16).…”
Section: Discussionmentioning
confidence: 99%
“…A preoperative SCT was performed in seven studies (Pate et al, 1996;Holden et al, 1992;Dong et al, 2017;Refai et al, 2014;Nikolic et al, 2007;Toker et al, 2007;Brunelli et al, 2001), in which different SCT protocols were used. Patients were asked 1) to climb the maximum number of steps at a pace of their own choice (Pate et al, 1996;Holden et al, 1992;Refai et al, 2014;Nikolic et al, 2007;Brunelli et al, 2001), 2) to climb five stairs with 20 steps as fast as they could without stopping to rest (Dong et al, 2017), or 3) to do their best during 2 stair-climbing exercises in which each flight of stairs was composed of 20 steps and climbing time was recorded (Toker et al, 2007). There were also differences between studies concerning test duration, step height, and number of steps.…”
Section: Stair-climb Testmentioning
confidence: 99%
“…Refai et al 7 ) reported an association between respiratory muscle weakness after lung resection and increased incidence of pulmonary complications. Recovery of respiratory muscle function after surgery is important because lung resection leads to impairments in these muscles.…”
Section: Discussionmentioning
confidence: 99%